Multilayer ceramic for electrostatic chuck and preparation method thereof

By optimizing the composition of ceramic slurry and adopting water-based gel casting and forming technology, combining laser invisible cutting technology to pre-process the give way space and sintering and shrinkage compensation space during the preparation of electrostatic chucks, the problems of shrinkage deformation and uneven distribution in the preparation of large-size electrostatic chucks are solved, and the preparation of electrostatic chucks with high flatness and uniform distribution is achieved.

CN119551971APending Publication Date: 2025-03-04ZHENGZHOU RES INST FOR ABRASIVES & GRINDING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411692630.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, when preparing large-size electrostatic chucks, the solid content of ceramic slurry is low, resulting in large shrinkage during drying, degreasing, and sintering, which easily causes warping and deformation, and the dielectric layer and electrode layer are unevenly distributed, resulting in poor adsorption effect.

Method used

By optimizing the composition of the ceramic slurry, using water-based gel casting and forming technology to prepare ceramic substrates, and pre-processing of the give way space and sintering and shrinkage compensation space inside the electrode layer and the ceramic substrate. The processing of these spaces is achieved using a laser invisible cutting process to reduce shrinkage deformation during sintering.

Benefits of technology

The electrostatic chuck with high flatness and uniform distribution of electrode layers is achieved, reducing deformation problems such as warping and bulging during sintering, and improving the stability and efficiency of the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of precise functional ceramic parts, and particularly relates to multilayer ceramic for an electrostatic chuck and a preparation method of the multilayer ceramic. According to the preparation method of the multilayer ceramic, a ceramic biscuit is formed in a water-based gel tape casting mode, and then the compact aluminum oxide multilayer co-fired ceramic is prepared through the steps of cross-linking curing, lamination, degreasing, sintering and the like. According to the method, the shrinkage rate of the ceramic biscuit in the curing process is reduced by optimizing the components of the ceramic slurry, the abdicating space corresponding to the electrode structure is machined in advance, and the space for compensating the shrinkage of the ceramic in the sintering process is machined in the ceramic substrate in advance by adopting the laser stealth cutting process; the deformation problems of warping, bulging and the like in the multi-layer ceramic sintering process are solved, and then the electrostatic chuck which is high in flatness and uniform in electrode layer distribution is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of precision functional ceramic parts, and in particular relates to a multilayer ceramic for an electrostatic chuck and a preparation method thereof. Background Art

[0002] The electrostatic chuck is a ceramic component that uses electrostatic adsorption to stably hold the wafer. It is an essential precision ceramic component in semiconductor etching, PVD, CVD and other processes. It consists of three parts: dielectric layer, electrode layer and base. The dielectric layer and electrode layer are the functional core of the electrostatic chuck. When in use, the dielectric layer and electrode layer are required to have high flatness and uniform distribution to achieve a uniform adsorption effect.

[0003] At present, the dielectric layer and electrode layer of the electrostatic chuck are mostly prepared by tape casting, followed by screen printing of electronic paste, lamination, and finally isostatic pressing and high-temperature co-firing. This process has low preparation cost and can be quickly applied to industrial production. However, in recent years, with the development of large-scale wafer size (12-inch and above specifications are becoming the mainstream), the requirements for the preparation process of electrostatic chucks are getting higher and higher. The existing process for preparing large-sized electrostatic chucks has the following problems: (1) The solid content of the traditional ceramic slurry used for casting is relatively low (the volume fraction is in the range of 50-55%), and the shrinkage during drying, degreasing and sintering is large (15-20%), which can easily cause warping and deformation; (2) The electronic slurry is directly screen-printed on the substrate plane, and then laminated and pressed, which inevitably leads to: ① After pressing, the multi-layer ceramic electrode layer area is raised at the micron scale, resulting in uneven distribution of the ceramic layer and the electrode layer; ② During the degreasing process, the middle part is blocked by gas, resulting in slow or untimely removal of organic matter and carbonization to the inside; ② During the high-temperature sintering (it can also be degreased and then sintered) process, the multi-layer ceramic layers will not be tightly bonded, and bulging and warping and deformation will occur after firing due to the difference in shrinkage between the dielectric layer and the electrode layer.

[0004] However, the existing public patents are all about optimizing the assembly structure of the electrostatic chuck, but rarely provide a detailed explanation of the preparation of the core component multilayer ceramics, especially how to control its shrinkage and deformation.

[0005] Therefore, in order to solve the above problems, the raw materials, preparation process parameters, etc. of the multilayer ceramics for the electrostatic chuck are adjusted in the present invention, in order to improve the performance of the prepared multilayer ceramics. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a multilayer ceramic for an electrostatic chuck and a preparation method thereof, which reduces the shrinkage rate of the ceramic blank during the solidification process by optimizing the ceramic slurry composition, pre-processes a clearance space corresponding to the electrode structure, and uses a laser invisible cutting process to pre-process a space inside the ceramic substrate to compensate for the shrinkage of the ceramic during the sintering process, thereby reducing deformation problems such as warping and bulging during the sintering process of the multilayer ceramic, thereby preparing an electrostatic chuck with high flatness and uniformly distributed electrode layers.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A multilayer ceramic for an electrostatic chuck and a preparation method thereof, comprising the following steps:

[0009] (1) forming ceramic green bodies 1 and 2 by water-based gel casting;

[0010] (2) The ceramic green body 1 and the ceramic green body 2 prepared in step (1) are cross-linked and cured to obtain ceramic substrate 1 and ceramic substrate 2;

[0011] (3) screen printing electrode slurry on the surface of the ceramic substrate 1 to obtain an electrode layer;

[0012] (4) processing a clearance space corresponding to the electrode layer structure on the surface of the ceramic substrate 2, and processing a sintering shrinkage compensation space inside the ceramic substrate 1 and / or the ceramic substrate 2;

[0013] (5) laminating the ceramic substrate 1 and the ceramic substrate 2, and performing isostatic pressing to obtain a multilayer ceramic pre-sintered body;

[0014] (6) Degreasing the multilayer ceramic pre-fired body of step (5) and sintering it under a protective atmosphere to obtain a dense multilayer co-fired ceramic.

[0015] Furthermore, in step (1), the water-based gel tape-casting method is to sequentially add a dispersant, a gel monomer, a cross-linking agent and a plasticizer into deionized water, stir and dissolve, add ceramic powder, and after ball milling and vacuum degassing, add a catalyst and an initiator to obtain a gel slurry, and then tape-cast the gel slurry to obtain ceramic blanks 1 and 2.

[0016] Furthermore, the dispersant is 0.2-0.5% of the mass of the ceramic powder, the gel monomer is 4-6% of the mass of the ceramic powder, the cross-linking agent is 0.4-0.6% of the mass of the ceramic powder, the plasticizer is 4-6% of the mass of the ceramic powder, the deionized water is 10-15% of the mass of the ceramic powder, the catalyst is 0.01-0.03% of the mass of the ceramic powder, and the initiator is 0.01-0.03% of the mass of the ceramic powder.

[0017] Furthermore, in the above-mentioned water-based gel casting method, the ball milling time is 2-5 hours, the ball milling speed is 150-300 r / min, the vacuum degassing time is 2-6 minutes, and the catalyst and initiator are evenly added by means of a peristaltic pump.

[0018] Furthermore, the ceramic powder includes a ceramic powder aggregate and a sintering aid mixed in the ceramic powder aggregate, wherein the ceramic powder aggregate is a powder selected from alumina powder, aluminum nitride powder and yttrium oxide powder or a mixture thereof, wherein a mixed powder selected from magnesium oxide powder, silicon oxide powder, calcium oxide powder and yttrium oxide powder is added as a sintering aid; the ceramic powder aggregate and the sintering aid are not yttrium oxide powder at the same time; the ceramic powder has a median particle size of 1-3 microns, a sphericity of ≥0.80, a particle size distribution distance of 1.20-2.0, and a specific surface area of ​​the powder dispersed in water of 0.8-1.3m 2 / cm 3 .

[0019] More preferably, the median particle size of the ceramic powder is 1.8-2.2 microns, the particle size distribution distance is 1.45-1.50, and the specific surface area of ​​the powder dispersed in water is 0.9-1.1m 2 / cm 3 .

[0020] Furthermore, the gel monomer is acrylamide, the crosslinking agent is N-N'methylenebisacrylamide, the dispersant is at least one of polyacrylic acid and polymethacrylic acid, the plasticizer is polyvinyl alcohol, the catalyst is tetramethylethylenediamine or tetramethylacetamide, and the initiator is 2-5wt% ammonium persulfate aqueous solution.

[0021] Furthermore, in step (2), the cross-linking and curing conditions are: temperature 21-30°C, time 20-40 min, and humidity 60%-80% during the cross-linking and curing process to prevent excessive temperature or low humidity from causing the surface to dry too quickly or peel, thereby causing defects in the green body.

[0022] Further preferably, in step (2), after curing, the curing effect can be enhanced by keeping the temperature at 70-80°C for 20-30 minutes.

[0023] Furthermore, in step (3), a screen printing machine is used for screen printing. The specific process method adopts conventional means in the prior art and is not the inventive point of the present invention, so it will not be described in detail.

[0024] Furthermore, in step (3), the main component of the electrode slurry is metal powder, which can withstand a high temperature of 1600° C. in a reducing atmosphere; preferably, the metal powder can be a single powder or a composite powder such as tungsten powder, molybdenum powder, or manganese powder.

[0025] Furthermore, in step (3), the metal powder accounts for 80-90 wt % of the electrode slurry, and the remaining components are organic solvents.

[0026] Furthermore, the components and mass percentages of the organic solvent are 93%-96% of terpineol, 3%-6% of ethyl cellulose, and 0.5%-1% of lecithin;

[0027] Alternatively, the components and mass percentages of the organic solvent may also be 68%-70% butyl carbitol acetate, 12%-15% ethyl cellulose, 6%-8% furoic acid, and 9%-10% fatty alcohol polyoxyethylene ether.

[0028] Furthermore, in step (4), the clearance space is realized by laser processing, and the depth of the clearance space is controlled by controlling the shrinkage of the green body after isostatic pressing, so that the ceramic substrate 1 and the ceramic substrate 2 are tightly matched after isostatic pressing.

[0029] Furthermore, in step (4), a laser invisible cutting process is used to process sintering shrinkage compensation space inside the ceramic substrate 1 and / or the ceramic substrate 2. Specifically, the laser is focused inside the ceramic substrate 1 and / or the ceramic substrate 2 to produce relatively regular and evenly distributed gaps, and the sintering shrinkage compensation of the ceramic substrate is achieved by controlling the shape and size of the gaps.

[0030] Furthermore, a large number of micrometer-scale point spaces are processed in the dielectric layer part (ie, the ceramic substrate 1). The existence of these strip grooves and point spaces is used to release the shrinkage stress during the sintering process, and also provides a channel for the removal of organic matter.

[0031] Furthermore, in step (4), the shrinkage compensation space inside the ceramic substrate 1 and / or ceramic substrate 2 can be specifically discrete dots, grooves or specific shapes, and its spatial volume is approximately proportional to the solid content of the ceramic slurry. The higher the solid content of the ceramic slurry, the smaller (less) the shrinkage compensation space that needs to be pre-processed.

[0032] Furthermore, in step (5), the lamination is performed by laminating the ceramic substrate 2 onto the upper surface of the ceramic substrate 1, and the multilayer ceramic pre-fired body formed is laminated in the order of ceramic layer 1, electrode layer, and ceramic layer 2 from bottom to top; the isostatic pressing pressure is 20-40MPa, the holding time is 5-20min, and the temperature is room temperature (25±5°C).

[0033] Furthermore, in step (6), the temperature is kept at 600-1200°C for 2-4 hours for degreasing treatment, and then the temperature is increased to 1560-2000°C at a rate of 1-5°C / min, and sintered for 1-4 hours in a protective atmosphere to obtain a dense multilayer co-fired ceramic to prevent oxidation of the metal electrode from affecting the electrical properties.

[0034] Furthermore, in step (6), the protective atmosphere is a hydrogen reducing atmosphere or a nitrogen reducing atmosphere.

[0035] Further preferably, in step (6), debinding and sintering can also be completed in one step by adjusting the heating curve.

[0036] Further preferably, the shrinkage of the ceramic product after sintering is 10-14%.

[0037] Further preferably, the present invention designs the particle size and the ratio so that the solid content of the slurry reaches 60-65wt%.

[0038] Furthermore, based on a general inventive concept, the present invention also provides a multilayer ceramic for an electrostatic chuck prepared by the above method.

[0039] Furthermore, based on a general inventive concept, the present invention also provides application of the multilayer ceramic in manufacturing an electrostatic chuck.

[0040] Specifically, the electrostatic chuck is prepared by precision machining the multilayer ceramic.

[0041] The multilayer ceramic prepared by the present invention can be assembled with an electrostatic chuck base to prepare an electrostatic chuck, and can meet the use requirements of the electrostatic chuck in a wafer etching environment.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] 1. The present invention utilizes gel tape casting technology to prepare ceramic substrates, and can achieve net size molding during the cross-linking and curing process, greatly reducing the shrinkage deformation of the ceramic from slurry to green body.

[0044] 2. The present invention controls the diameter and sphericity of the ceramic powder to make the particles densely packed, and optimizes the amount of dispersant added, thereby ultimately increasing the solid content of the ceramic green body, reducing the shrinkage rate during the curing, degreasing and sintering processes, and further reducing the shrinkage deformation during the preparation process.

[0045] 3. The preparation method of the present invention pre-processes a clearance space corresponding to the electrode structure on the surface of the upper ceramic substrate, and at the same time uses a laser invisible cutting process to pre-process a space of a certain shape and size inside the ceramic substrate. In this way, firstly, the clearance space allows the ceramic and the electrode to shrink synchronously, ensuring the bonding flatness between the electrode layer and the ceramic layer; secondly, the compensation space inside the ceramic substrate has the following advantages: ① It is conducive to the discharge of internal organic matter during the degreasing process of the ceramic substrate, avoiding organic matter residue; ② It inhibits the stress concentration caused by continuous densification during the sintering process, which leads to shrinkage, bulging and warping at the macro level; ③ The existence of this space can inhibit the excessive growth or abnormal growth of grains.

[0046] In short, the existence of the concession space and the internal compensation space greatly improves the problem of poor flatness of ceramics after sintering, and provides a raw material basis for the production of electrostatic chucks. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 A diagram showing the positional relationship between the ceramic substrate 1, the ceramic substrate 2 and the electrode layer of the present invention;

[0048] Figure 2 FIG. 1 is a diagram of the groove structure inside the ceramic substrate 1 in Example 1;

[0049] Figure 3 FIG. 1 is a diagram showing the groove structure inside the ceramic substrate 1 in Example 2;

[0050] Figure 4 Schematic diagram of the microstructure inside the ceramic substrate 1 or the ceramic substrate 2 in Example 1 and Example 2. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not limit the present invention.

[0052] In order to make the description of the present disclosure more detailed and complete, the following provides an illustrative description of the implementation and specific embodiments of the present invention; however, this is not the only form of implementing or using the specific embodiments of the present invention. The implementation covers the features of multiple specific embodiments and the method steps and sequences used to construct and operate these specific embodiments. However, other specific embodiments can also be used to achieve the same or equivalent functions and step sequences.

[0053] Unless otherwise specified, the instruments and equipment used in the following examples are all commercially available conventional instruments and equipment; other reagents and materials used are all commercially available conventional reagents and materials unless otherwise specified.

[0054] Example 1

[0055] Example 1 provides a method for preparing a multilayer ceramic for an electrostatic chuck, and the specific steps are as follows:

[0056] (1) A ceramic green body 1 and a ceramic green body 2 are formed on a casting device (a common device in the prior art is used, and it is not the inventive point of the present invention, so it will not be described in detail) by using a water-based gel casting method;

[0057] Specifically, the water-based gel casting method is to sequentially add a dispersant, a gel monomer, a crosslinking agent and a plasticizer into deionized water, stir and dissolve, add ceramic powder, ball mill for 5 hours (ball mill speed 200r / min), vacuum degassing for 4 minutes, add a catalyst and an initiator to obtain a gel slurry, and then cast the gel slurry to obtain ceramic blanks 1 and ceramic blanks 2;

[0058] The dispersant is 0.2% of the mass of the ceramic powder, the gel monomer is 4% of the mass of the ceramic powder, the cross-linking agent is 0.4% of the mass of the ceramic powder, the plasticizer is 5% of the mass of the ceramic powder, the deionized water is 12% of the mass of the ceramic powder, the catalyst is 0.02% of the mass of the ceramic powder, and the initiator is 0.02% of the mass of the ceramic powder. The catalyst and the initiator are evenly added by a peristaltic pump.

[0059] The ceramic powder comprises a ceramic powder aggregate and a sintering aid mixed in the ceramic powder aggregate. The ceramic powder aggregate is alumina, wherein the sintering aid contains MgO-SiO2-CaO accounting for 1.5wt% of the alumina (the mass ratio of the three is 10:45:45). The median particle size of the ceramic powder is 1.8-2.2 microns, the sphericity is ≥0.80, the particle size distribution diameter is 1.45-1.50, and the specific surface area of ​​the powder is 0.9-1.1m 2 / cm 3 ;

[0060] The gel monomer is acrylamide, the crosslinking agent is N-N'methylenebisacrylamide, the dispersant is polyacrylic acid, the plasticizer is polyvinyl alcohol, the catalyst is tetramethylethylenediamine, and the initiator is a 5wt% aqueous solution of ammonium persulfate;

[0061] (2) cross-linking and curing the ceramic blanks 1 and 2 prepared in step (1) at a temperature of 25° C. for 38 minutes (humidity of 60% to 80% to prevent excessive temperature or low humidity from causing the surface to dry too quickly or peel, thereby causing body defects) to obtain alumina ceramic substrates 1 and 2;

[0062] (3) Screen printing (using a screen printer for printing, the specific process method adopts conventional means in the prior art, and is not the inventive point of the present invention, so it is not repeated here) electrode slurry (the main component of the electrode slurry is metal powder, which can withstand a high temperature of 1600° C. under a reducing atmosphere, and the metal powder accounts for 80-90wt% of the electrode slurry, and the remaining components are organic solvents, and the components and mass percentages of the organic solvents are 94.5% of pine alcohol, 5% of ethyl cellulose, and 0.5% of lecithin. The metal powder can be tungsten, molybdenum, manganese or a composite powder thereof. In this embodiment, the metal powder is tungsten powder) is formed on the upper surface of the ceramic substrate 1 to form a tungsten electrode with a thickness of 25 μm, which is the electrode layer;

[0063] (4) Figure 1 As shown, a clearance space corresponding to the tungsten electrode is processed on the lower surface of the ceramic substrate 2, and the depth of the clearance space is 23.75 μm; the clearance space is realized by laser processing, and the depth of the clearance space is controlled by controlling the shrinkage of the green body after isostatic pressing, so that the ceramic substrate 1 and the ceramic substrate 2 are closely matched after isostatic pressing;

[0064] A laser invisible cutting process is used to process several uniformly distributed shrinkage compensation grooves (such as Figure 2 As shown in the figure, the sintering shrinkage compensation space is used. Specifically, the laser is focused inside the ceramic substrate 1 and the ceramic substrate 2 to generate relatively regular and evenly distributed gaps, and the sintering shrinkage compensation of the ceramic substrate 1 and the ceramic substrate 2 is achieved by controlling the shape and size of the gaps;

[0065] At the same time, if Figure 4 As shown, a large number of micrometer-scale point spaces are processed in the dielectric layer part (i.e., the ceramic substrate 1). The existence of these strip grooves and point spaces is used to release the shrinkage stress during the sintering process, and also provides a channel for the removal of organic matter;

[0066] The shrinkage compensation space inside the ceramic substrate 1 and the ceramic substrate 2 can be a discrete dot, a groove or a specific shape, and its space volume is approximately proportional to the solid content of the ceramic slurry. The higher the solid content of the ceramic slurry, the smaller (less) the shrinkage compensation space that needs to be pre-processed.

[0067] (5) Then, the ceramic substrate 1 and the ceramic substrate 2 are laminated and subjected to isostatic pressing to obtain a multilayer ceramic pre-sintered body;

[0068] In step (5), the lamination is to laminate the ceramic substrate 2 onto the upper surface of the ceramic substrate 1, and the multilayer ceramic pre-sintered body is laminated in the order of ceramic layer 1, electrode layer, and ceramic layer 2 from bottom to top; the isostatic pressing pressure is 30 MPa, the holding time is 10 min, and the temperature is room temperature (25±5°C);

[0069] (6) The multilayer ceramic pre-fired body of step (5) is kept at 800°C for 2 hours for degreasing. The degreasing multilayer ceramic body is heated to 1600°C at a rate of 1.5°C / min and sintered for 2 hours in a hydrogen reducing atmosphere (to avoid oxidation of the metal electrode affecting the electrical properties) to obtain a dense alumina multilayer co-fired ceramic. Compared with the ceramic substrate before preparation, the shrinkage rate of the ceramic product after sintering is 12%. In this embodiment, the solid content of the slurry reaches 60-65wt% through the design of particle size and ratio.

[0070] In addition, the multi-layer co-fired ceramics can be precisely processed to prepare an electrostatic chuck through post-processing.

[0071] Performance Testing

[0072] The density of the alumina multilayer co-fired ceramics sintered in Example 1 was tested by the Archimedes drainage method, and the result was 3.88 g / cm 3 The bending strength of alumina multilayer co-fired ceramics was tested using an electronic universal testing machine, and the result was 350MPa.

[0073] The flatness of alumina multilayer co-fired ceramics was tested using a three-dimensional coordinate measuring machine, and the result was 20μm.

[0074] After testing, the dielectric layer resistivity of alumina multilayer co-fired ceramics is 10 16 Ω·cm, which meets the requirements for the use of Coulomb type electrostatic chuck.

[0075] Example 2

[0076] Example 2 provides a method for preparing a multilayer ceramic for an electrostatic chuck, and the specific steps are as follows:

[0077] (1) A ceramic green body 1 and a ceramic green body 2 are formed on a casting device (a common device in the prior art is used, and it is not the inventive point of the present invention, so it will not be described in detail) by using a water-based gel casting method;

[0078] Specifically, the water-based gel tape casting method is to sequentially add a dispersant, a gel monomer, a crosslinking agent and a plasticizer into deionized water, stir and dissolve, add ceramic powder, ball mill for 2 hours (ball mill speed 200r / min), vacuum degassing for 6 minutes, add a catalyst and an initiator to obtain a gel slurry, and then tape cast the gel slurry to obtain ceramic blanks 1 and ceramic blanks 2;

[0079] The dispersant is 0.5% of the mass of the ceramic powder, the gel monomer is 5% of the mass of the ceramic powder, the cross-linking agent is 0.55% of the mass of the ceramic powder, the plasticizer is 5% of the mass of the ceramic powder, the deionized water is 10% of the mass of the ceramic powder, the catalyst is 0.03% of the mass of the ceramic powder, and the initiator is 0.03% of the mass of the ceramic powder. The catalyst and the initiator are evenly added by a peristaltic pump.

[0080] The ceramic powder comprises a ceramic powder aggregate and a sintering aid mixed in the ceramic powder aggregate. The ceramic powder aggregate is aluminum nitride, wherein the yttrium oxide sintering aid accounts for 2 wt% of the aluminum nitride. The ceramic powder has a median particle size of 1.8-2.2 microns, a sphericity of ≥0.80, a particle size distribution distance of 1.45-1.50, and a powder specific surface area of ​​0.9-1.1 m 2 / cm 3 ;

[0081] The gel monomer is acrylamide, the crosslinking agent is N-N'methylenebisacrylamide, the dispersant is polyacrylic acid, the plasticizer is polyvinyl alcohol, the catalyst is tetramethylacetamide, and the initiator is a 5wt% aqueous solution of ammonium persulfate;

[0082] (2) curing the ceramic blanks 1 and 2 prepared in step (1) at a temperature of 30° C. for 20 min (with a humidity of 60% to 80% to prevent the surface from drying out too quickly or peeling due to excessive temperature or low humidity, thereby causing body defects) to obtain aluminum nitride ceramic substrates 1 and 2;

[0083] (3) Screen printing (using a screen printer for printing, the specific process method adopts conventional means in the prior art, and is not the inventive point of the present invention, so it is not repeated) electrode slurry (the main component of the electrode slurry is metal powder, the metal powder can withstand a high temperature of 1600°C under a reducing atmosphere, the metal powder accounts for 80-90wt% of the electrode slurry, and the remaining components are organic solvents, the components and mass percentages of the organic solvents are 69% butyl carbitol acetate, 14% ethyl cellulose, 7% furoic acid, and 10% fatty alcohol polyoxyethylene ether. The metal powder can be tungsten, molybdenum, manganese or a composite powder thereof. In this embodiment, the metal powder is a mixed powder of tungsten powder and molybdenum powder, wherein the mass ratio of tungsten powder to molybdenum powder is 80:20) to form a tungsten-molybdenum composite slurry electrode with a thickness of 35μm, i.e., the electrode layer;

[0084] (4) a clearance space corresponding to the tungsten-molybdenum composite slurry electrode is processed on the surface of the ceramic substrate 2, and the depth of the clearance space is 33.25 μm; the clearance space is realized by laser processing, and the depth of the clearance space is controlled by controlling the shrinkage of the green body after isostatic pressing, so that the ceramic substrate 1 and the ceramic substrate 2 are closely matched after isostatic pressing;

[0085] The laser invisible cutting process is used to process grooves (such as Figure 3 As shown) as a shrinkage compensation space to compensate for the warping and deformation caused by the mismatch between the expansion coefficients of the metal electrode layer and the ceramic;

[0086] At the same time, if Figure 4 As shown, numerous micrometer-scale point spaces are processed in the dielectric layer part (ceramic substrate 1). The existence of these strip grooves and point spaces is used to release the shrinkage stress during the sintering process, and also provides a channel for the removal of organic matter;

[0087] The shrinkage compensation space inside the ceramic substrate 1 can be specifically a discrete dot, a groove or a specific shape, and its space volume is approximately proportional to the solid content of the ceramic slurry. The higher the solid content of the ceramic slurry, the smaller (less) the shrinkage compensation space that needs to be pre-processed.

[0088] (5) Then, the ceramic substrate 1 and the ceramic substrate 2 are laminated and subjected to isostatic pressing to obtain a multilayer ceramic pre-sintered body;

[0089] In step (5), the lamination is to laminate the ceramic substrate 2 onto the upper surface of the ceramic substrate 1, and the multilayer ceramic pre-sintered body is laminated in the order of ceramic layer 1, electrode layer, and ceramic layer 2 from bottom to top; the isostatic pressing pressure is 20 MPa, the holding time is 10 min, and the temperature is room temperature (25±5°C);

[0090] (6) The multilayer ceramic pre-fired body of step (5) is kept at 1200°C for 2 hours for degreasing. The degreasing multilayer ceramic body is heated to 1860°C at a rate of 5°C / min and sintered for 2 hours in a nitrogen reducing atmosphere (to avoid oxidation of the metal electrode affecting the electrical properties) to obtain a dense aluminum nitride multilayer co-fired ceramic. Compared with the ceramic substrate before preparation, the shrinkage rate of the ceramic product after sintering is 10%. In this embodiment, the solid content of the slurry reaches 60-65wt% through the design of particle size and ratio.

[0091] In addition, the multi-layer co-fired ceramics can be precisely processed to prepare an electrostatic chuck through post-processing.

[0092] Performance Testing

[0093] The density of the aluminum nitride multilayer co-fired ceramics after sintering in Example 2 was tested by the Archimedes drainage method, and the result was 3.21 g / cm 3 The bending strength of aluminum nitride multilayer co-fired ceramics was tested using an electronic universal testing machine, and the result was 380MPa.

[0094] The flatness of aluminum nitride multilayer co-fired ceramics was tested using a three-coordinate measuring machine, and the result was 15μm.

[0095] After testing, the dielectric layer resistivity of aluminum nitride multilayer co-fired ceramics is 10 10 Ω·cm, meeting the requirements for use of JR type electrostatic chuck.

[0096] Application Examples

[0097] The multilayer co-fired ceramic prepared in Example 1 or Example 2 is assembled with an electrostatic chuck base, and the wafer is subjected to adsorption, desorption and etching tests in a simulated plasma environment. After 500 tests, the adsorption force, adsorption and desorption response, and life span can meet the use requirements of the wafer etching environment, indicating that the multilayer co-fired ceramic prepared in the present invention has good mechanical properties and can meet the use requirements of the electrostatic chuck.

[0098] The above embodiments are examples of the implementation methods of the present invention, and the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a multilayer ceramic for an electrostatic chuck, characterized in that: The steps include: (1) forming ceramic green bodies 1 and 2 by water-based gel tape casting; (2) The ceramic green sheets 1 and 2 prepared in step (1) are cross-linked and cured to obtain ceramic substrates 1 and 2; (3) screen printing electrode slurry on the surface of the ceramic substrate 1 to obtain an electrode layer; (4) a clearance space corresponding to the electrode layer structure is processed on the surface of the ceramic substrate 2, and a sintering shrinkage compensation space is processed inside the ceramic substrate 1 and / or the ceramic substrate 2; (5) laminating the ceramic substrate 1 and the ceramic substrate 2, and performing isostatic pressing to obtain a multilayer ceramic pre-sintered body; (6) Degreasing the multilayer ceramic pre-fired body of step (5) and sintering it under a protective atmosphere to obtain a dense multilayer co-fired ceramic.

2. The preparation method according to claim 1, characterized in that In step (1), the water-based gel casting method is to sequentially add a dispersant, a gel monomer, a crosslinking agent and a plasticizer into deionized water, stir and dissolve, add ceramic powder, and after ball milling and vacuum degassing, add a catalyst and an initiator to obtain a gel slurry, and then cast the gel slurry to obtain ceramic blanks 1 and ceramic blanks 2; The dispersant accounts for 0.2-0.5% of the mass of the ceramic powder, the gel monomer accounts for 4-6% of the mass of the ceramic powder, the cross-linking agent accounts for 0.4-0.6% of the mass of the ceramic powder, the plasticizer accounts for 4-6% of the mass of the ceramic powder, the deionized water accounts for 10-15% of the mass of the ceramic powder, the catalyst accounts for 0.01-0.03% of the mass of the ceramic powder, and the initiator accounts for 0.01-0.03% of the mass of the ceramic powder.

3. The preparation method according to claim 2, characterized in that: The ceramic powder comprises a ceramic powder aggregate and a sintering aid mixed in the ceramic powder aggregate, wherein the ceramic powder aggregate is one of alumina powder, aluminum nitride powder and yttrium oxide powder or a mixture thereof, wherein one or more of magnesium oxide powder, silicon oxide powder, calcium oxide powder and yttrium oxide powder are added as a sintering aid; the ceramic powder aggregate and the sintering aid are not yttrium oxide powder at the same time; the ceramic powder has a median particle size of 1-3 microns, a sphericity of ≥0.80, a particle size distribution diameter of 1.20-2.0, and a powder specific surface area of ​​0.8-1.3m 2 / cm 3 .

4. The preparation method according to claim 2, characterized in that: The gel monomer is acrylamide, the crosslinking agent is N-N'methylenebisacrylamide, the dispersant is at least one of polyacrylic acid and polymethacrylic acid, the plasticizer is polyvinyl alcohol, the catalyst is tetramethylethylenediamine or tetramethylacetamide, and the initiator is 2-5wt% ammonium persulfate aqueous solution.

5. The preparation method according to claim 1, characterized in that: In step (2), the cross-linking and curing conditions are: temperature 21-30°C, time 20-40 min.

6. The preparation method according to claim 1, characterized in that: In step (3), the main component of the electrode slurry is metal powder; the metal powder can be a single powder or a composite powder of tungsten powder, molybdenum powder, and manganese powder.

7. The preparation method according to claim 1, characterized in that: In step (5), the isostatic pressure is 20-40 MPa, and the pressure is maintained for 5-20 minutes.

8. The preparation method according to claim 1, characterized in that: In step (6), the temperature is kept at 600-1200°C for 2-4 hours for degreasing treatment, and then the temperature is increased to 1560-2000°C at a rate of 1-5°C / min, and sintered for 1-4 hours in a protective atmosphere to obtain a dense multilayer co-fired ceramic.

9. Multilayer ceramic for electrostatic chuck prepared by the method according to any one of claims 1 to 8.

10. Use of the multilayer ceramic according to claim 9 in the manufacture of an electrostatic chuck.

Citation Information

Patent Citations

  • Method for producing electrostatic chuck and electrostatic chuck

    CN102731072A

  • A method of preparing an aluminium nitride ceramic substrate by gel casting

    CN104649677A

  • Composite insulator substrate, preparation method thereof and electrostatic chuck device

    CN118324496A

  • Method for manufacturing ceramic substrate and ceramic substrate

    US20210367578A1

  • Multilayer devices and methods of manufacturing

    WO2018140972A1